Digital literacy: exploration of social media-based Arabic language learning - Aulia Mustika Ilmiani; Mukhtar I Miolo (Politeknik Negeri Bali, 2021)
Social media is often used as a learning tool, one of which is Arabic learning. This study aims to explore social media-based Arabic learning carried out by Arabic Language Education study program lecturers at IAIN Palangka Raya. By using descriptive qualitative research methods, this study describes the steps for implementing Arabic language learning which is carried out using social media, such as accessing, selecting, understanding, analyzing, verifying, evaluating and producing. The findings in this study describe that social media is used as: First, as a publication forum for project-based assignments; Second, as a means of digital literacy to obtain information; Third, as a way for students to optimize social media as a medium for literacy. The social media used in learning Arabic in the PBA IAIN Palangka Raya study program are; Whatsapp is used as a learning resource for Maharah Istima, Instagram is used as a learning resource in Maharah Kalam. Facebook is used as a learning resource for Maharah Qiraah and Kitabah. Meanwhile, Youtube is mostly used for the publication of project-based assignments. Further research recommended is the effectiveness of using social media in improving Arabic learning skills, as well as digital literacy-based Arabic learning using other information technologies.